The analysis of self-attitude in cosmetological patients with low self-esteem - Юдін, Михайло Анатолійович (ScienceRise: Medical Science, 2016)
The features of self-attitude in cosmetological patients were studied in the research. Contingent and methods of research. The study was carried out on the base of medical center “CA-CLINIC” (city Kiev) during 2014 – 2016 years. Testing included 204 women, who addressed for cosmetological help. The interrogated persons were divided in groups depending on the level of self-esteem: the main group included persons with low self-esteem (MG, n=108) and group of comparison – women with normal self-esteem (CG, n=96). Psychodiagnostic instrument is the questionnaire of self-attitude by V.V. Stolin and S.R. Pantileev. Results. It was revealed, that women with low self-esteem had lower levels of global self-attitude, self-respect, autosympathy, self-interest, expected attitude of others, self-confidence, readiness to self-perception, self-understanding, self-management and the highest one – self-accusation as opposite to the interrogated with normal self-esteem. The women with low self-esteem in their self-attitude expressed the negative setting as to the own Me, incertitude in own physical and psychological qualities, did not understood their negative features or overstated their value, were inclined to self-accusation and expressed the acute desire to change themselves. Self-attitude in women with low self-esteem was disharmonic and characterized with high level of self-rejection, decrease of self-respect and self-understanding, alienation of subjectively negative features, exaggeration of own defects. Conclusions. Cosmetological patients with low self-esteem form the separate category of clients and need the use of medical-psychological arrangements, directed on harmonization of disharmonic self-attitude